2009
DOI: 10.1007/bf03195684
|View full text |Cite
|
Sign up to set email alerts
|

Screening of the 17p11.2–p12 region in a large cohort of patients with Charcot-Marie-Tooth (CMT) disease or hereditary neuropathy with liability to pressure palsies (HNPP)

Abstract: Within the last decade, numerous methods have been applied to detect the most common mutation in patients affected with Charcot-Marie-Tooth (CMT) disease, i.e. submicroscopic duplication in the 17p11.2--p12 region. In 1993, another neuropathy - known as hereditary neuropathy with liability to pressure palsies (HNPP) - has been shown to be caused by a 17p11.2--p12 deletion. Historically, Southern blot analysis was the first approach to identify CMT1A duplication or HNPP deletion. This time- and labor-consuming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
(15 reference statements)
1
9
0
Order By: Relevance
“…Nevertheless, PMP22 copy number determination identified a total of 7 families with deletion, thus the ratio of deletion to duplication is 1 to 5.7. This difference in the number of detected deletions and duplications is similar to the outcome of a European collaborative study by Nelis et al (1996), although there are publications that reported markedly higher and markedly lower ratios (Silander et al 1998;Kabzinska et al 2009). …”
Section: Discussionsupporting
confidence: 83%
“…Nevertheless, PMP22 copy number determination identified a total of 7 families with deletion, thus the ratio of deletion to duplication is 1 to 5.7. This difference in the number of detected deletions and duplications is similar to the outcome of a European collaborative study by Nelis et al (1996), although there are publications that reported markedly higher and markedly lower ratios (Silander et al 1998;Kabzinska et al 2009). …”
Section: Discussionsupporting
confidence: 83%
“…5 It is known that PMP22 gene dosage is related to clinical course of Charcot-Marie-Tooth disease type 1A and HNPP, 6 and HNPP patients have less dosage of PMP22 gene compared to healthy controls. 7 Our patient with elderly onset of HNPP might have had PMP22 gene dosage close to healthy controls; however, the dosage of the patient was not evaluated. Further studies are needed to elucidate the genotype related to elderly onset of HNPP.…”
Section: Discussionmentioning
confidence: 90%
“…The Q-PCR reaction was performed on the ABI-7500 Real-Time PCR system (Applied Biosystems). The relative dosage (RQ) of the PMP22 gene ranges from 0.700 to 1.090 in normal individuals (two copies of the PMP22 gene), from 0.359 to 0.595 in HNPP patients (one copy of the PMP22 gene), and from 1.176 to 2.324 in CMT1A patients (three copy of the PMP22 gene) [ 5 ].…”
Section: Methodsmentioning
confidence: 99%